Effective group work with young people - Westergaard, Jane , 1959- (Maidenhead, England : Open University Press, 2009)
This book aims to improve the confidence of those working with young people and ensure that the 'group experience' is a positive one for both the practitioner and the group of young people
1. The role of youth support workers with groups of young people -- 2. Applying learning theory to personal learning and development group work -- 3. Assessing needs and identifying a topic -- 4. Setting aims and objectives leading to positive outcomes -- 5. Activities to enable personal learning and development -- 6. Getting the structure of sessions right -- 7. Skills to facilitate personal learning and development -- 8. group dynamics -- 9. Managing challenging behavior and attitudes -- 10. Evaluating personal learning and development
Includes bibliographical references and index
Keywords: Group work in education